Epidemiological profile of seropositive pregnant women - Sales, Ashlley Coutinho Schelck; Bittencourt , Cynthia Bruzi; Araújo, Gabriella Coutinho de; Oliveira, Ghiezzy Berbert de; Oliveira, Kathleen Monteiro de; Palmeira, Odete Alves (Seven Editora, 2023)
Many women only find out that they have HIV when they are pregnant and perform the tests in the prenatal period, while some become aware in the postpartum, where the tests are also performed on the baby to detect the positive serum, taking into account that not all pregnant women perform these tests during pregnancy or, in some cases, do not have at least the knowledge of their condition until the time of delivery. This is documentary research, which aims to trace the epidemiological profile of seropositive pregnant women, who attended and conceived their children in a reference maternity for high-risk delivery in the South Fluminense Region - RJ. Method: data collection in the medical records of pregnant women with HIV registered between January 2015 and December 2017.  Results: it was evidenced that all the pregnant women in the research have a low socioeconomic situation, level of education up to high school, predominates the age group of up to 30 years, brown in color, and do not have a defined occupation. Conclusion: the epidemiological profile of pregnant women has changed. On the other hand, over the years studies and treatments have been developed to reduce vertical transmission of HIV and ensure that the baby has a better quality of life. Brazil, through the Ministry of Health, has invested in women's health care policies, creating prenatal care protocols with the provision of kits for HIV serology testing, to increasingly contribute to the eradication of vertical transmission of this infection. DOI:https://doi.org/10.56238/alookdevelopv1-024